Deletion of Long Isoform of Eukaryotic Elongation Factor 1Bδ Leads to Audiogenic Seizures and Aversive Stimulus-Induced Long-Lasting Activity Suppression in Mice - Kaitsuka, Taku; Kiyonari, Hiroshi; Shiraishi, Aki; Tomizawa, Kazuhito; Matsushita, Masayuki (Frontiers in Molecular Neuroscience, 2018)
Alternative splicing enables a gene to give rise to diverse protein products. The Eef1d gene produces two isoforms: a short isoform that encodes translation elongation factor 1Bdelta (eEF1Bdelta1), and a long isoform that encodes the heat shock-responsive transcription factor eEF1BdeltaL. Previously, we found that eEF1BdeltaL was a splice variant that was specific to the brain and testis, and the protein encoded is thought to have a function in the central nervous system. In this study, we generated knockout (KO) mice of C57BL/6J background that selectively lacked a specific exon in Eef1d for the long isoform. These KO mice lacked eEF1BdeltaL, but not eEF1Bdelta1, in the brain. Although the KO mice showed normal anxiety-related and learning behavior in behavioral tests, some showed severe seizures in response to loud sounds (90 dBA), an audiogenic seizures (AGS) response. Furthermore, after the KO mice had been subjected to the fear conditioning test, they showed remarkably decreased locomotor activity in their home cage and in the open-field and elevated plus-maze tests. After the fear conditioning test, a significant decrease in brain weight, atrophy of the hippocampus and midbrain, and reduced cortical layer thickness were observed in the KO mice. We also found a compensatory increase in the eEF1Bdelta1 level and elevated protein synthesis with the induction of endoplasmic reticulum stress markers in these mice. Our results suggest that eEF1BdeltaL has an important role in normal brain function especially when exposed to external stimuli.